2011
DOI: 10.2141/jpsa.010093
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression of Muscle-Specific Ubiquitin Ligase, Atrogin-1/MAFbx, Positively Correlates with Skeletal Muscle Proteolysis in Food-Deprived Broiler Chickens

Abstract: A relationship between skeletal muscle proteolysis and mRNA expression of atrogin-/MAFbx, a muscle-specific ubiquitin ligase, was examined in food-deprived broiler chickens. In response to food deprivation for and h, body and muscle weights decreased in a time-dependent manner. Muscle free N -methylhistidine content, an index of myofibrillar proteolysis, was . -fold and . -fold greater than that of fed controls following and h of food deprivation, respectively. Gene expression of atrogin-/MAFbx drastically inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 20 publications
4
27
0
Order By: Relevance
“…We previously showed that myostatin expression was significantly suppressed by fasting in chickens, whereas atrogin-1 expression was significantly induced (Saneyasu et al, 2015). Similar results were reported concerning myostatin (Guernec et al, 2004) and atrogin-1 (Ohtsuka et al, 2011) in broiler chickens. It is therefore possible that myostatin is not involved in the upregulation of atrogin-1 expression in the chicken skeletal muscle.…”
Section: Discussionsupporting
confidence: 84%
“…We previously showed that myostatin expression was significantly suppressed by fasting in chickens, whereas atrogin-1 expression was significantly induced (Saneyasu et al, 2015). Similar results were reported concerning myostatin (Guernec et al, 2004) and atrogin-1 (Ohtsuka et al, 2011) in broiler chickens. It is therefore possible that myostatin is not involved in the upregulation of atrogin-1 expression in the chicken skeletal muscle.…”
Section: Discussionsupporting
confidence: 84%
“…Atrogin-1/MAFbx plays a critical role in muscle proteolysis, and the level of atrogin-1/MAFbx gene expression is a reliable index of muscle proteolysis in chicken (Ohtsuka et al, 2011). Although it is well known that IGF-I have a regulatory effect on the expression of atrogin-1/MAFbx in mammalian skeletal muscle, its effect in chicken muscle cells is largely unknown.…”
Section: Resultsmentioning
confidence: 99%
“…These observations suggested that clenbuterol might affect either proteolysis in skeletal muscle or expression of atrogin-1/MAFbx. In addition, Ohtsuka et al (2011) reported that gene expression of atrogin-1/MAFbx positively correlates with skeletal muscle proteolysis in chickens, hence it is possible that a single administration of clenbuterol to neonatal chicks resulted in the increase in the weight of skeletal muscle by decrease in atrogin-1 mRNA expression. Further studies are needed to gain more information about the molecular mechanisms underlie that hypertrophic effects of clenbuterol on skeletal muscle of neonatal chicks.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Navegantes et al (2001) reported that clenbuterol treatment decreases proteolysis in the skeletal muscle of rats. In chicken, gene expression of atrogin-1/MAFbx positively correlates with skeletal muscle proteolysis (Ohtsuka et al, 2011). Therefore, we also examined gene expression of atrogin-1/MAF box as a representative of proteolysis related proteins in skeletal muscle of chicks.…”
Section: Introductionmentioning
confidence: 99%